2000
DOI: 10.1029/2000gl011422
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic constraints on the rigidity and relative motion of Eurasia and North America

Abstract: Abstract.GPS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 18 publications
8
64
0
1
Order By: Relevance
“…The location of the new geologic pole is close to that of the NUVEL-1A EU^NA pole, but has much smaller con¢dence limits that re£ect the signi¢-cant increase in the number of data used to derive the new angular velocity vector. The northerly location for the new best-¢tting geodetic pole is similar to previously published GPS-and VLBIbased models for EU^NA motion [10,15,18,19].…”
Section: Eurasia^north Americasupporting
confidence: 65%
“…The location of the new geologic pole is close to that of the NUVEL-1A EU^NA pole, but has much smaller con¢dence limits that re£ect the signi¢-cant increase in the number of data used to derive the new angular velocity vector. The northerly location for the new best-¢tting geodetic pole is similar to previously published GPS-and VLBIbased models for EU^NA motion [10,15,18,19].…”
Section: Eurasia^north Americasupporting
confidence: 65%
“…[34] A total of 71 stations was selected to represent plate motions, starting from the choice as in published studies of the plate kinematics (Table 4 and Figure 1b) [Dixon et al, 1996;Kogan et al, 2000;Beavan et al, 2002;Sella et al, 2002;Kreemer et al, 2003;Steblov et al, 2003;Prawirodirdjo and Bock, 2004]. In contrast with our selection, Argus [2007] included many more GPS stations in western Europe; we preferred less dense sampling of that region to ensure a proper contribution of Siberian stations to the estimated motion of the Eurasian plate.…”
Section: Choice Of Plates and Of Plate-defining Stationsmentioning
confidence: 99%
“…[7] The model of the plate kinematics presented here addresses the problem debated since the beginning of the space geodesy, How big are disagreements between the current plate motions and the motions averaged over several million years, the ''geologic'' timescale [Argus and Heflin, 1995;Larson et al, 1997;DeMets and Dixon, 1999;Kogan et al, 2000;Beavan et al, 2002;Sella et al, 2002;Calais et al, 2003a;Steblov et al, 2003]? Some discrepancies between geodetic and geologic models were resolved due to improvements in the geologic plate model based on updated marine magnetic surveys [DeMets and Dixon, 1999;Calais et al, 2003a].…”
Section: Introductionmentioning
confidence: 99%
“…1). No fewer than six different Euler rotation poles for the Amurian/Eurasia motion have been proposed to date Seno, 1998, 2000;Heki et al, 1999;Kogan et al, 2000;Sella et al, 2002;Calais et al, 2003;Kreemer et al, 2003), whereas the Amurian plate has been shown to have a different motion from that of the Eurasian plate (Petit and Fournier, 2005).…”
Section: Introductionmentioning
confidence: 99%